Endocrinological roles for testosterone in resistance exercise responses and adaptations - Hooper, D. R.; Kraemer, W. J.; Focht, B. C.; Volek, J. S.; DuPont, W. H.; Caldwell, L. K.; Maresh. C. M. (Sports Medicine, 2017)
Chronic increases in testosterone levels can significantly increase hypertrophy and strength, as has been demonstrated by pharmacological intervention. However, decreases in basal testosterone levels can have the opposite result, as has been seen in hypogonadal populations. Because of these profound effects on hypertrophy and strength, testosterone has often been studied in conjunction with resistance exercise to examine whether the endocrine system plays a role in adaptations to the stimulus. Whereas some studies have demonstrated a chronic increase in basal testosterone, others have failed to find an adaptation to regular resistance exercise. However, improvements in strength and hypertrophy appear to be possible regardless of the presence of this adaptation. Testosterone has also been shown to acutely rise immediately following an acute resistance exercise bout. While this substantial mobilization of testosterone is brief, its effects are seen for several hours through the upregulation of the androgen receptor. The role of this acute response at present is unknown, but further study of the non-genomic action and possible intracrinological processes is warranted. This response does not seem to be necessary for resistance training adaptations to occur either, but whether this response optimizes such adaptations has not yet been determined.